2016
DOI: 10.1093/carcin/bgw107
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide analysis of gene–caffeine consumption interaction on basal cell carcinoma

Abstract: Animal models have suggested that oral or topical administration of caffeine could inhibit ultraviolet-induced carcinogenesis via the ataxia telangiectasia and rad3 (ATR)-related apoptosis. Previous epidemiological studies have demonstrated that increased caffeine consumption is associated with reduced risk of basal cell carcinoma (BCC). To identify common genetic markers that may modify this association, we tested gene-caffeine intake interaction on BCC risk in a genome-wide analysis. We included 3383 BCC cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Most studies find that regular coffee intake increases blood pressure slightly and raises plasma cholesterol and homocysteine levels [1], whereas coffee consumption is associated with a reduced incidence of type 2 diabetes mellitus [2], a decrease in inflammatory markers [3] and improved endothelial function [4]. Caffeine consumption also affects pain modulation [5] and interacts with skin carcinomas, with some evidence pointing at a protective effect of caffeine on malignant melanoma [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies find that regular coffee intake increases blood pressure slightly and raises plasma cholesterol and homocysteine levels [1], whereas coffee consumption is associated with a reduced incidence of type 2 diabetes mellitus [2], a decrease in inflammatory markers [3] and improved endothelial function [4]. Caffeine consumption also affects pain modulation [5] and interacts with skin carcinomas, with some evidence pointing at a protective effect of caffeine on malignant melanoma [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Fluoxetine synergizes with TMZ to induce the CHOP-dependent ER stress-related apoptosis pathway in glioma cells (20). As for caffeine, it could inhibit ultraviolet-induced skin carcinogenesis via increasing a DNA repair gene (NEIL3) expression and increasing the ataxia telangiectasia and rad3 (ATR)-related apoptosis (21). Caffeine could induce premature chromosome condensation and result in cell death in root meristems of Vicia faba (22).…”
Section: Figurementioning
confidence: 99%
“…Literature reviews showed that 14 genes have were related with cancers (Ahn, et al, 2019;Chiou, et al, 2019;Ishiuchi, et al, 2002;Li, et al, 2019;Li, et al, 2016;Li, et al, 2017;Liu, et al, 2019;Malik, et al, 2019;Michiels, et al, 2007;Oakes, et al, 2017;Wang, et al, 2019;Yao, et al, 2018;Yu, et al, 2015). Among these genes, KRAS, NRAS and TP53 are common oncogenes in cancer studies, while CDH10, GABRG2, GRIA2, KCNK9, SOX5, ERCC5, HIST1H4H, LRRTM4 were recently verified as cancer-related gene by wet-lab experiments.…”
Section: Case Study: Predicting Oncogenes In the Ovarian Cancermentioning
confidence: 99%